Applications of analytical techniques to clinical practice : assessment of chemical changes in patients with acute lymphoblastic leukemia following methotrexate administration - Miketová, Petra; Moore, Ida M. (Ki); Hockenbery, Marilyn; Khailová, Ludmila; Jelínek, David; Kernag, Casey; Schram, Karl H.; Hutter, John; Kaemingk, Kristine L (Univerzita Pardubice, 2006)
The application of the following methods was described for the purpose of exploration of different cerebrospinal fluid biomarkers related to the cognitive impairment in children suffering from acute lymphoblastic leukemia and receiving methotrexate as part of the treatment regimen: gas chromatography/mass spectrometry was employed to measure the levels of homovanillic acid and vanilmandelic acid: twodimensional electrophoresis was used to find the changes in protein profiles present in cererebrospinal fluid: and high performance liquid chromatography was utilized to measure the levels of cerebrospinal fluid ceramides. The overall goal of this project was to utilize different analytical techniques in order to monitor chemical changes in cerebrospinal fluid associated wuth the administered amount of methotrexate.
Keywords: analytické techniky; klinická praxe; leukemie; biomarkery; sledování; plynová chromatografie; Hmotnostní spektrometrie